The role of macrophage migration inhibitory factor in autoimmune liver disease. Issue 2 (20th December 2013) - Assis, David N.; Leng, Lin; Du, Xin; Zhang, Clarence K.; Grieb, Gerrit; Merk, Melanie; Garcia, Alvaro Baeza; McCrann, Catherine; Chapiro, Julius; Meinhardt, Andreas; Mizue, Yuka; Nikolic‐Paterson, David J.; et al.
<x xml:space="preserve">Abstract</x> The role of the cytokine, macrophage migration inhibitory factor (MIF), and its receptor, CD74, was assessed in autoimmune hepatitis (AIH) and primary biliary cirrhosis (PBC). Two MIF promoter polymorphisms, a functional −794 CATT5‐8 microsatellite repeat (rs5844572) and a −173 G/C single‐nucleotide polymorphism (rs755622), were analyzed in DNA samples from over 500 patients with AIH, PBC, and controls. We found a higher frequency of the proinflammatory and high‐expression −794 CATT7 allele in AIH, compared to PBC, whereas lower frequency was found in PBC, compared to both AIH and healthy controls. MIF and soluble MIF receptor (CD74) were measured by enzyme‐linked immunosorbent assay in 165 serum samples of AIH, PBC, and controls. Circulating serum and hepatic MIF expression was elevated in patients with AIH and PBC versus healthy controls. We also identified a truncated circulating form of the MIF receptor, CD74, that is released from hepatic stellate cells and that binds MIF, neutralizing its signal transduction activity. Significantly higher levels of CD74 were found in patients with PBC versus AIH and controls. Conclusions: These data suggest a distinct genetic and immunopathogenic basis for AIH and PBC at the MIF locus. Circulating MIF and MIF receptor profiles distinguish PBC from the more inflammatory phenotype of AIH and may play a role in pathogenesis and as biomarkers of these diseases. (Hepatology 2014;59:580–591)